2002
DOI: 10.1039/b200571a
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxyl radical FeIII complex of cis,cis-1,3,5-tris(3′,5′-di-tert-butylsalicylaldimino)cyclohexane, spectro-electrochemical and structural studies

Abstract: Complexationof cis,cis-1,3,5-tris(3Ј,5Ј-di-tert-butylsalicylaldimino)cyclohexane (H 3 tBu 2 saltach) with M III (M ‫؍‬ Fe and Ga) followed by subsequent one electron oxidation results in the formation of stable phenoxylradical complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Both complexes crystallized with five‐coordinate, high‐spin iron(III) centers that are surrounded by fully deprotonated ligands to yield the neutral species (Table S1 and S2 in the Supporting Information). The bond lengths and angles were consistent with other examples in the literature 3c,g,i. 6b,c The ORTEP diagrams with selected bond lengths and angles for 1 and 2 are shown in Figure 1.…”
Section: Methodssupporting
confidence: 88%
“…Both complexes crystallized with five‐coordinate, high‐spin iron(III) centers that are surrounded by fully deprotonated ligands to yield the neutral species (Table S1 and S2 in the Supporting Information). The bond lengths and angles were consistent with other examples in the literature 3c,g,i. 6b,c The ORTEP diagrams with selected bond lengths and angles for 1 and 2 are shown in Figure 1.…”
Section: Methodssupporting
confidence: 88%
“…[58] For instance, it has been shown that tert-butyl substituents at the ortho and para positions of the phenolates facilitate one-electron oxidation to the corresponding phenoxyl radicals, because these substituents decrease the oxidation potential of the phenolates and provide enough steric bulk to suppress bimolecular decay reactions of the generated phenoxyl radicals. [59] Several groups have prepared metal-phenoxyl complexes giving new insights into the chemical factors that govern the generation and stability of this type of radicals, [60] temperature X-ray crystallography. [61] In addition, o-iminobenzosemiquinonate(1 -) anions are paramagnetic (S = 1/2) ligands that couple either ferro-or antiferromagnetically when coordinated to a paramagnetic transition metal ion, depending on the symmetry of the magnetic d orbital of the metal ion.…”
Section: Phenoxyl Ligandsmentioning
confidence: 99%
“…In reference to previous phenolate-tach complexes, 8 both the first and second reversible oxidation processes observed in the CV of 1 are assigned to the production of first one and then a second phenoxyl-radical. It appears, therefore, that 1 undergoes two reversible ligand-based, phenolate to phenoxyl-radical redox processes, and no metal-based processes are observed within the redox range of the experiment.…”
Section: 1517mentioning
confidence: 99%
“…8 The Fe III complexes exhibit reversible ligand-based oxidation processes to give bound phenoxyl radical species at remarkably low oxidation potentials. The complexes are, however, coordinatively saturated at the metal centre, limiting their ability to act as oxidation catalysts.…”
Section: Introductionmentioning
confidence: 99%